Synergistic effects of technological innovation, industrial structure upgrading, and ecological environment optimization—evidence from China - Yang, Jiaojiao; Wang, Ting (Frontiers in Ecology and Evolution, 2023)
The benign interaction between technological innovation, industrial structure, and ecological environment optimization is important for the sustainable development of China's economy. Based on panel data from 30 provinces (municipalities) in China from 2003 to 2019, a coupling coordination degree (CCD) model was adopted to evaluate the coordinated development level of the technological innovation-industrial structure-ecological environment system (TIE). Fixed-effect models were used to explore the subsystem impact on the coupling coordination level. A fully modified least-squares(FMOLS) method was used to analyze TIE subsystem interactions. The results show the following: (1) The coordinated development level of TIE has steadily improved. The CCD of the TIE was high in the east, flat in the center, and low in the west. (2) Subsystem development significantly and positively affected the degree of coupling coordination. The ecological environmental impact on the coordinated development level was the largest in the eastern regions and the influence of technological innovation on the coordinated development level was the largest in the central and western regions. (3) Industrial advancement had a positive impact on technological innovation in 30 provinces as a whole, and in the eastern, central, and western regions. A "U"-shaped relationship was found between technological innovation and industrial advancement in all 30 provinces, and in the eastern, central provinces. Industrial rationalization, industrial advancement, and technological innovation can promote the improvement of the ecological environment in all 30 provinces, and the eastern, central, and western regions.